REPRESENTASI FUNGSIONAL-2 DI l^p - Yosafat Eka Prasetya Pangalela; Hendra Gunawan (Jurnal Ilmiah Matematika dan Pendidikan Matematika (JMP), 2012)
In this paper, the concept of 2-functionals will be introduced. The concept of bounded linear 2-functionals will be studied as an extension. We also discuss the 2-dual space of , which is the space of bounded linear 2-functionals of completed by some norm.